Front Cover: A Convenient and Stable Heterogeneous Nickel Catalyst for Hydrodehalogenation of Aryl Halides Using Molecular Hydrogen (ChemSusChem 5/2022). Issue 5 (15th February 2022) - Leonard, David K.; Ryabchuk, Pavel; Anwar, Muhammad; Dastgir, Sarim; Junge, Kathrin; Beller, Matthias
Abstract : The Front Cover shows how the "Dehalogenato" spell allows to replace halogen atoms by hydrogens, using a heterogeneous nickel catalyst supported on titanium oxide in the presence of dihydrogen. The practicality of this catalyst system is demonstrated by the complete dehalogenation of environmentally hazardous and polyhalogenated substrates such as polybrominated diphenyl ethers and others. More information can be found in the Research Article by D. K. Leonard, P. Ryabchuk, et al .